2016
DOI: 10.1057/978-1-137-53339-5
|View full text |Cite
|
Sign up to set email alerts
|

Culturally Responsive and Socially Just Leadership in Diverse Contexts

Abstract: translation, reprinting, reuse of illustrations, recitation, broadcasting, reproduction on microfilms or in any other physical way, and transmission or information storage and retrieval, electronic adaptation, computer software, or by similar or dissimilar methodology now known or hereafter developed. The use of general descriptive names, registered names, trademarks, service marks, etc. in this publication does not imply, even in the absence of a specific statement, that such names are exempt from the relevan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…Whereas contemporary research has identified similar leadership actions (Hargons et al, 2017; Lopez, 2015; McKibben et al, 2017; Theoharis, 2007; Wang, 2018), the current findings offer a broader understanding of those actions. Of all the actions and findings within this socially just and culturally responsive leadership, the inclusion of group-systems was the most distinct contribution to both the counseling-specific and socially just and culturally responsive leadership literature, given the lack of accounting for group-system dynamics in leadership at large, especially socially just and culturally responsive leadership (Lopez, 2016; McKibben et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Whereas contemporary research has identified similar leadership actions (Hargons et al, 2017; Lopez, 2015; McKibben et al, 2017; Theoharis, 2007; Wang, 2018), the current findings offer a broader understanding of those actions. Of all the actions and findings within this socially just and culturally responsive leadership, the inclusion of group-systems was the most distinct contribution to both the counseling-specific and socially just and culturally responsive leadership literature, given the lack of accounting for group-system dynamics in leadership at large, especially socially just and culturally responsive leadership (Lopez, 2016; McKibben et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, it could be part of associations’ or institutions’ strategic planning for or self-evaluation of socially just and culturally responsive leadership practices (Hargons et al, 2017; Singh et al, 2010). By providing various stakeholders with the current findings, time for self-reflection, and evaluations of themselves and/or their groups, associations, or organizations, counseling professionals can further develop and revise ways to advance SJCRCL-based practices (Lopez, 2016; Hargons et al, 2017).…”
Section: Implications For Practice Advocacy Education and Trainingmentioning
confidence: 99%
See 2 more Smart Citations
“…Few leaders and teachers in today's schools have acquired the understanding, knowledge, and skills needed to work effectively in culturally diverse educational settings through conventional teacher education or professional development programs (Lopez, 2016). Many do not feel confident to work with students whose cultural and linguistic backgrounds differ from theirs, though scholars and practitioners have clearly indicated that this type of professional training and praxis is critical for providing newcomer students the pedagogic, linguistic, social, cultural, and psychologic support and services they needed (Khalifa, Gooden & Davis, 2016;Leblanc, 2017;Shields, 2010;Yong, Madsen, & Yong, 2010).…”
Section: Social Injustice Toward Immigrant and Refugee Studentsmentioning
confidence: 99%